The introduction of the financial ombudsman scheme as an alternative to dispute resolution in the Islamic financial services industry in Malaysia - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah (International Islamic University Malaysia, 2016)
With the enactment of the Islamic Financial Services Act 2013 (IFSA 2013) in Malaysia, the dispute resolution landscape has been transformed to reflect more on effective dispute settlement that would ensure consumer protection without prejudicing the interests of the financial service providers. The Central Bank of Malaysia, as the main regulatory body for the Islamic financial services industry in Malaysia, indicates that the Financial Mediation Bureau (FMB) is in the process of implementing the Financial Ombudsman Scheme (FOS). In analysing this statutory by-product of IFSA 2013, this paper examines the transformation of FMB as a structured statutory body in resolving Islamic finance disputes. In addition, the dispute resolution structure of FMB under the FOS is evaluated and appreciated. A comparative legal analysis is provided in a separate section by examining the structures of other financial ombudsmen as available in other jurisdictions. The examples are taken from other financial ombudsmen practices as applied in selected Commonwealth countries, i.e., Ireland, United Kingdom, and Pakistan.